Adiponectin association with T‐cadherin protects against neointima proliferation and atherosclerosis. Issue 4 (6th January 2017) - Fujishima, Yuya; Maeda, Norikazu; Matsuda, Keisuke; Masuda, Shigeki; Mori, Takuya; Fukuda, Shiro; Sekimoto, Ryohei; Yamaoka, Masaya; Obata, Yoshinari; Kita, Shunbun; Nishizawa, Hitoshi; Funahashi, Tohru; et al.
Abstract : Adiponectin, an adipocyte‐derived protein abundant in the circulation, is thought to be protective against atherosclerosis. However, it is not fully understood how the association of adiponectin with vascular cells and its antiatherogenic effect are connected. In this study, T‐cadherin was essential for accumulation of adiponectin in the neointima and atherosclerotic plaque lesions, and the adiponectin–T‐cadherin association protected against vascular injury. In the apolipoprotein E‐knockout (ApoE‐KO) mice, adiponectin and T‐cadherin colocalized on en‐dothelial cells and synthetic smooth muscle cells in the aortic intima. Notably, aortic adiponectin protein disappeared in T‐cadherin/ApoE double‐knockout (Tcad/ApoE‐DKO) mice with significant elevation of blood adiponectin concentration. Furthermore, in Tcad/ApoE‐DKO mice, carotid artery ligation resulted in a significant increase of neointimal thickness compared with ApoE‐KO mice. Finally, on a high‐cholesterol diet, Tcad/ApoE‐DKO mice increased atherosclerotic plaque formation, despite a 5‐fold increase in plasma adiponectin level compared with that in ApoE‐KO mice. In vitro, knockdown of T‐cadherin from human aortic smooth muscle cells (HASMCs) with synthetic phenotype significantly reduced adiponectin accumulation on HASMCs and negated the inhibitory effect of adiponectin on proinflammatory change. Collective evidence showed that adiponectin accumulates in the vasculature via T‐cadherin, and the adiponectin–T‐cadherin association plays a protective role against neointimal and atheroscle‐rotic plaque formations. —Fujishima, Y., Maeda, N., Matsuda, K., Masuda, S., Mori, T., Fukuda, S., Sekimoto, R., Yamaoka, M., Obata, Y., Kita, S., Nishizawa, H., Funahashi, T., Ranscht, B., Shimomura, I. Adiponectin association with T‐cadherin protects against neointima proliferation and atherosclerosis. FASEB J . 31, 1571–1583 (2017) www.fasebj.org